2007
DOI: 10.1111/j.1467-9280.2007.01978.x
|View full text |Cite
|
Sign up to set email alerts
|

When the Need to Belong Goes Wrong

Abstract: People possess an innate need to belong that drives social interactions. Aberrations in the need to belong, such as social anhedonia and social anxiety, provide a point of entry for examining this need. The current study used experience-sampling methodology to explore deviations in the need to belong in the daily lives of 245 undergraduates. Eight times daily for a week, personal digital assistants signaled subjects to complete questionnaires regarding affect, thoughts, and behaviors. As predicted, higher leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(104 citation statements)
references
References 20 publications
8
92
1
3
Order By: Relevance
“…In line with our hypotheses and with the literature on the ambivalent response to social proximity in both BPD (Stepp et al, 2009; Stiglmayr et al, 2005) and social anxiety disorder (that is highly comorbid with APD; Brown et al, 2007; Russell et al, 2011), we found participants with BPD or APD to display mixed affective reactions to social proximity: Some moods improved; other got worse. This ambivalent pattern stood in contrast to more uniformly positive reactions found among HCs when in social proximity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with our hypotheses and with the literature on the ambivalent response to social proximity in both BPD (Stepp et al, 2009; Stiglmayr et al, 2005) and social anxiety disorder (that is highly comorbid with APD; Brown et al, 2007; Russell et al, 2011), we found participants with BPD or APD to display mixed affective reactions to social proximity: Some moods improved; other got worse. This ambivalent pattern stood in contrast to more uniformly positive reactions found among HCs when in social proximity.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, in a daily diary study of undergraduates, SAD symptoms were associated with greater self-consciousness and a preference to being alone when interacting with unfamiliar (but not familiar) people (Brown et al, 2007). Taken together, these studies suggest that social interactions elicit ambivalent reactions in those with SAD, who experience social interactions as more aversive, but also as more desirable, than non-SAD individuals, at least under some conditions (e.g., Brown et al, 2007; Kashdan & Collins, 2010; Russell et al, 2011). It is likely that those with APD show a similar pattern of responses.…”
Section: Interpersonal Difficulties and Reactions To Social Proximitymentioning
confidence: 96%
See 1 more Smart Citation
“…Having a positive sense of belonging has been found to enhance interpersonal, professional and academic success, improve self-concept, to be a protective factor for suicide and overall to be vital to psychological functioning (Brown, Silvia, Myin-Germeys, & Kwapil, 2007; Drolet, Arcand, Ducharme, & Leblanc, 2013; Hagerty, Williams, Coyne, & Early, 1996; Kissane & McLaren, 2006). The data underscore that meaningful connections and presence of others in the lives of persons with schizophrenia can impact well-being and mental health.…”
Section: Resultsmentioning
confidence: 99%
“…Ambulatory monitoring techniques such as the Experience Sampling Method (ESM) or Ecological Momentary Assessment (EMA) have been increasingly applied over the last decade to study of a range of psychiatric disorders, including mood disorders (Myin-Germeys et al, 2003;Peeters et al, 2006), psychosis (Delespaul et al, 2002;deVries and Delespaul, 1989;Granholm et al, 2007;Kimhy et al, 2006;Myin-Germeys et al, 2001, personality disorders (Ebner-Priember et al, 2006;Farmer et al, 2004;Loewenstein et al, 1987;Stein, 1996), eating disorders (Hilbert and Tuschen-Caffi er, 2007;Smyth et al, 2007;Stein and Corte, 2003), social anxiety (Brown et al, 2007;Kashdan and Steger, 2006;Lee et al, 2006) and substance use (Cooney et al, 2007;Freedman et al, 2006;Hopper et al, 2006;Krahn et al, 2005;Lukasiewicz et al, 2005;Swendsen et al, 2000). A principal advantage of this approach is that it allows researchers to assess symptom expression in a manner that is often inaccessible to standard hospital or laboratory protocols, and to model complex within-person processes over time.…”
Section: Introductionmentioning
confidence: 99%